The effect of grant receipt on start-up size: Evidence from plant level data - Sourafel Girma; Holger Görg; Aoife Hanley; Eric Strobl (Kiel Institute for the World Economy (IfW), 2010)
In this paper we use plant level data on the start-up size of new plant entries and detailed information on the grants received by such plants in order to investigate whether grant receipt encourages plants to start-up with more employment than without support. The data relate to manufacturing plants in the Republic of Ireland, where industrial policy has a long history of using discretionary grants to encourage employment growth. We use a matching procedure to deal with the issue of selectivity into grant receipt, and a quantile regression estimator to allow for different effects of grants on plants depending on their position in the start-up size distribution. Our results provide evidence that grants do indeed encourage plants to start-up larger. We also find that this effect is generally higher for foreign than for domestic plants, and that it differs for plants at different quantiles of the start-up size distribution.
Keywords: H2; L2; 330; Grants; subsidies; entry; start-up size; Industriesubvention; Subvention; Unternehmensgründung; Betriebsgröße; Verarbeitendes Gewerbe; Irland